Geology and geomorphology of the pantanal basin - Assine, Mario L. [UNESP]; Merino, Eder R. [UNESP]; Pupim, Fabiano N. [UNESP]; Warren, Lucas V. [UNESP]; Guerreiro, Renato L.; McGlue, Michael M. (Springer Nature, 2016)
What is an inlier sedimentary basin? What are the main mechanisms of sedimentary infilling? How do the depositional systems behave? And last, but certainly not the least, what geological events occurred in the last million years and continue to take place in the Pantanal area today? These issues are considered in this chapter, based on available geological, geomorphological, and geochronological datasets. The Pantanal is an active sedimentary basin with numerous faults and associated earthquakes. Movements along these faults cause subsidence on blocks within the basin, generating depressions that are highly susceptible to flooding, and also create accommodation space for sediment storage. One hypothesis on the origin of the Pantanal Basin relates the processes of subsidence with tectonic activity in the Andean orogen and foreland system during the Quaternary. Alternatively, the lack of geochronological data leaves open the possibility that the basin formed much earlier, perhaps during an interval of widespread tectonism in Brazil during the Eocene. The modern Pantanal depositional tract is composed of the Paraguay River trunk system, numerous fluvial megafans and interfan floodplains, and thousands of lakes, many of them integral to the Nhecolândia landscape. The Pantanal’s geomorphology is most likely the product of climatic fluctuations and environmental changes that have been occurring since the Late Pleistocene. Relict morphologic features like paleochannels have been preserved on the surfaces of abandoned lobes on several large fluvial megafans. After a period dominated by arid conditions in the Late Pleistocene, the Pantanal area experienced an episode of humidification and increasing fluvial discharge in the Early Holocene. This process promoted important modifications in the extant drainage system, for example, the avulsion of the Paraguay River that caused the Nabileque paleomeander belt to be abandoned. The landscape and sedimentary deposits of Pantanal Basin are “living” geologic records of changing rivers, avulsions, floods, and climate changes that occurred in the last several thousand years. Understanding the dynamics of these transitions is critical for unveiling the geologic history of the world’s largest tropical wetland.
Keywords: Avulsion; Fluvial megafans; Nhecolândia; Pantanal basin; Tectonics and sedimentation